Pattern of contraceptive use at a family planning clinic in Southern Nigeria - Nonye Enyidah, Esther I.; Enyidah, Nonyenim S.; Eshemogie, Chisomaga (International Journal of Research in Medical Sciences, 2020)
Background: Contraception is very important in preventing unwanted pregnancies thereby reducing maternal and child mortality as well as improving the lives of women and their families. This paper aims to determine the pattern of contraceptive usage, uptake rates of the contraceptives, the socio-demographic characteristics and sources of information on contraceptive use at the Rivers State University Teaching Hospital (RSUTH) during the study period. Methods: This was a retrospective study of clients’ records in family planning clinic at RSUTH over a period of ten years. Their records were retrieved, reviewed; data extracted, coded and analyzed using the statistical package for social sciences (SPSS) IBM version 25.0. Results: There were 1893 contraceptive acceptors attending family planning clinic between 1st January, 2008 and 31st December, 2017 in the centre. The uptake rate of the contraceptives throughout the study period was on the downward trend. Over half of the clients (60.7%) were within the age range of 30-39years and 6 (0.3%) were below 20 years. Age range for the study was 19-51years. Majority of the users (66.1%) were multipara. Modal parity was para 3 and 1862 clients (98.4%) had formal education. Most of the clients were married 1814 (95.8%) and of Christian religion 1813 (95.7%). Most preferred contraceptive method was the intrauterine contraceptive device (IUCD), 814 (43%). Clinical personnel were the commonest source of information accounting for 1425 (75.3%). Conclusions: There was a downward trend in the use of contraceptives during the study period. Most clients were in their thirties, married, educated and multiparous.